Monitoring of the cavitation inception speed and sound pressure level of the model propeller using accelerometer attached to the model ship in the cavitation tunnel. (15th December 2022) - Han, HyungSuk; Jeon, Soohong; Kim, Yonghoon; Lee, Chungwon; Lee, Dongnyuk; Lee, Gahyang; Lee, Sukku
Abstract: The naval vessel uses sonar to detect and identify the enemy under the water. Therefore, it is necessary to reduce the noise of the own ship to detect the enemy ship, and also to avoid detection by the enemy's sonar system. To reduce the noise of the ship, cavitation of the propeller should be prohibited; and when engaged in anti-submarine warfare operations, the ship must sail below the cavitation inception speed. Therefore, the cavitation inception speed and sound pressure radiating from the propeller should be monitored in real time. In this research, an algorithm is developed for the condition-based monitoring of the propeller sound using an accelerometer on the hull above the propeller. Highlights: The monitoring algorithm of the propeller sound and CIS using an accelerometer is developed. The algorithm is verified with model scale test in the cavitation tunnel with the model ship. The monitoring by visual inspection is conducted at the same time as that by accelerometer.